2018
DOI: 10.1016/j.ijhydene.2018.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production from bio-oil: A thermodynamic analysis of sorption-enhanced chemical looping steam reforming

Abstract: This is a repository copy of Hydrogen production from bio-oil: a thermodynamic analysis of sorption-enhanced chemical looping steam reforming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Additionally, the bio-oil also contains a certain amount of other oxygenated substances, such as sugars, ethers, anhydrides, etc. With regard to the bio-oil, the overall SR reaction under ideal conditions can be expressed as follows: (1) This means that the theoretical maximum amount of H 2 produced from the bio-oil is 0.104 gH 2g bio-oil…”
Section: The Properties and Compositions Of Bio-oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the bio-oil also contains a certain amount of other oxygenated substances, such as sugars, ethers, anhydrides, etc. With regard to the bio-oil, the overall SR reaction under ideal conditions can be expressed as follows: (1) This means that the theoretical maximum amount of H 2 produced from the bio-oil is 0.104 gH 2g bio-oil…”
Section: The Properties and Compositions Of Bio-oilmentioning
confidence: 99%
“…Given the importance of environmental issues and sustainable energy development, a lot of efforts are being made to exploit the sustainable biomass for producing hydrogen. 1,2 Biomass has the advantages of abundant reserves, wide sources, low price, carbon neutrality. The use of lignocellulosic waste to produce hydrogen can not only help to reduce CO 2 emissions, but also enable the waste to be recycled.…”
Section: Introductionmentioning
confidence: 99%
“…Concepturally, chemcial looping biomass processing is a low carbon technology that efficiently converts biomass to syngas for sustainable chemical production. [224] Additionally, other environmental aspects associated with the production and supply of biomasses, the life cycle of OCs and the disposal of ash, must also be understood by scientific approaches, for example, life cycle analysis (LCA). [225] The LCA study by Petrescu et al found that hydrogen produced from a Fe-based chemical looping process with simultaneous CO 2 Figure 13.…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…The application of such a hydrogen‐containing gas was limited. So, to obtain higher‐purity H 2 and reduce CO 2 emission, the concept of sorption‐enhanced steam reforming was put forward, by in‐situ adsorption of CO 2 (i.e., adding CO 2 sorbent into the reforming process) to displace the original equilibrium of the steam reforming reaction to the direction of H 2 production, and it has been widely studied in the reforming of methane 22‐24 and bio‐oil, 1,25‐28 with the obvious improvement of H 2 yield and concentration. So, the sorption‐enhanced steam reforming concept was extended in the H 2 production from RCOG, and the thermodynamic analysis on this enhanced process showed that the tar components can be converted efficiently and the H 2 amount can be improved to over 4.25 times of that in the original RCOG, with the H 2 concentration approaching 100% in the reformed COG 7 .…”
Section: Introductionmentioning
confidence: 99%